Association of Monocyte Chemoattractant Protein‐1 (MCP‐1)‐2518A>G Polymorphism with Susceptibility to Coronary Artery Disease: A Meta‐Analysis. (27th February 2015) - Bai, Xiao‐Yan; Li, Shujing; Wang, Miao; Qu, Xinjian; Hu, Gaolei; Xu, Zhaowei; Chen, Min; He, Guo‐Wei; Wu, Huijian
Summary We attempted to systematically elucidate the association between monocyte chemoattractant protein‐1 (MCP‐1) ‐2518A>G polymorphism and risk of coronary artery disease (CAD). Eligible studies were identified through PubMed, EBSCO, and Web of Science Databases. The magnitude of MCP‐1 polymorphism effect and its possible mode of action on CAD were estimated. The odds ratio (OR) with 95% confidence intervals (CI) were pooled in a specific genetic model to assess the association. A total of 21 studies were involved. There was significant gene effect on CAD risk in the overall population (likelihood ratio test: p < 0.0001). Patients with GG and AG genotypes had 1.435 (95% CI: 1.183–1.740) and 1.087 (95% CI: 1.008–1.172) times higher risk of CAD than those with AA genotype. These gene effects suggested a recessive model to be appropriate. The pooled OR was 1.362 (95% CI: 1.137–1.631; puncorrected = 0.001, pFDR = 0.005) in the recessive model. In the ethnicity‐stratified analysis, significant association was observed in the Caucasian population (OR = 1.492; 95% CI: 1.106–2.014; puncorrected = 0.009, pFDR = 0.015), whereas no statistical significant association was detected in the Asian population (adjusted p = 0.124). The results suggested that MCP‐1 ‐2518A>G polymorphism may be associated with susceptibility to CAD, especially in Caucasians.